2008
DOI: 10.11646/zootaxa.1780.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A new species of clawed frog (genus Xenopus) from the Itombwe Massif, Democratic Republic of the Congo: implications for DNA barcodes and biodiversity conservation

Abstract: Here we describe a new octoploid species of clawed frog from the Itombwe Massif of South Kivu Province, Democratic Republic of the Congo. This new species is the sister taxon of Xenopus wittei, but is substantially diverged in morphology, male vocalization, and mitochondrial and autosomal DNA. Analysis of mitochondrial "DNA barcodes" in polyploid clawed frogs demonstrates that they are variable between most species, but also reveals limitations of this type of information for distinguishing closely related spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…To test whether this is the case in African clawed frogs, we reviewed data on snout vent length (SVL) for the single phase callers (Table 1; including data from Kobel et al, 1996; Evans et al, 2008, 2011) and calculated the correlation coefficient between body length and both dominant frequencies. We found no significant correlation between SVL and DF1 ( r = 0.033, p = 0.9, N = 20) or DF2 ( r = 0.19, p = 0.45, N = 18; Pearson correlation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether this is the case in African clawed frogs, we reviewed data on snout vent length (SVL) for the single phase callers (Table 1; including data from Kobel et al, 1996; Evans et al, 2008, 2011) and calculated the correlation coefficient between body length and both dominant frequencies. We found no significant correlation between SVL and DF1 ( r = 0.033, p = 0.9, N = 20) or DF2 ( r = 0.19, p = 0.45, N = 18; Pearson correlation).…”
Section: Resultsmentioning
confidence: 99%
“…new tetraploid 1 and X . new tetraploid, have not yet been described and two, X. itombwensis and X. lenduensis , represent recent discoveries (Evans et al, 2008, 2011). Advertisement calls from 18 species have been published previously and our data agree with respect to call type for 13 of these (Vigny, 1979; Wetzel & Kelley, 1983; Fischer et al, 2000); for three species (Vigny, 1979), the reported waveforms are not detailed enough to compare call type.…”
Section: Discussionmentioning
confidence: 99%
“…The Itombwe Plateau harbors an unusually large number of endemic amphibians (Greenbaum and Kusamba, 2012), including recent species descriptions for Xenopus itombwensis (Evans et al, 2008) and Leptopelis anebos (Portillo and Greenbaum, 2014a). Haplotypes from Amietia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Many threatened and endemic species reside within the AR (Plumptre et al, 2007; Jenkins et al, 2013; Portillo et al, 2015), making it one of the most irreplaceable and important sites for conservation in Africa (Brooks et al, 2006). Many vertebrate species in the AR are morphologically cryptic and endemic to a small number of sites, including small mammals (Kerbis Peterhans et al, 2010; Demos et al, 2014), birds (Prigogine, 1971, 1977, 1978, 1984, 1985; Bowie et al, 2006), reptiles (Greenbaum et al, 2011, 2015a; Menegon et al, 2014) and amphibians (Laurent, 1964, 1972; Evans et al, 2008, 2011; Greenbaum and Kusamba, 2012; Portillo and Greenbaum, 2014a,b; Portillo et al, 2015). Viertel et al (2012) recently described tadpole morphology and chytrid fungal infections in a Ugandan population of A. ruwenzorica , but no previous studies have assessed AR Amietia populations with molecular data.…”
Section: Introductionmentioning
confidence: 99%
“…In anurans, approximately 56 cases of polyploidy have been described in species, populations, and as spontaneously originated polyploid individuals [5-12]. Although the tetraploidy (4x) is relatively common, cases of octoploidy (8x) and even dodecaploidy (12x) have been well documented, such as in the Xenopus species [13,14]. …”
Section: Introductionmentioning
confidence: 99%